Carrier Generation Engineering toward 18% Efficiency Organic Solar Cells by Controlling Film Microstructure. Issue 19 (7th April 2022) - Su, Yueling; Zhang, Lu; Ding, Zicheng; Zhang, Yi; Wu, Yin; Duan, Yuwei; Zhang, Qiang; Zhang, Jidong; Han, Yanchun; Xu, Zijian; Zhang, Rui; Zhao, Kui; et al.
Abstract: The single bulk‐heterojunction active layer based on non‐fullerene acceptors (NFAs) has dominated the power conversional efficiencies above 18% in state‐of‐the‐art organic solar cells (OSCs). However, a deep understanding of the relationship between charge carrier process and film microstructure remains unclear for emerging NFA OSCs. Herein, with the superstar PM6:Y6 blend as a model, the charge generation process in active layers is successfully manipulated by designing three different film microstructures, and they are correlated with the final photovoltaic performance in OSC devices. The amount of intermediate intra‐moiety excited states from the nanoscale Y6 aggregates can be effectively enhanced by controlling the phase separation domains and film crystallinity in the bicontinuous PM6:Y6 networks. This robustly improves the hole transfer, and thus promotes charge generation. As a result, the optimal films show superior device performance, that is, the high efficiencies of 16.53% and 17.98% for PM6:Y6‐ and D18:Y6‐based single junction OSCs, respectively. The results presented here give a rational guide for optimizing the charge carrier process through controlling morphological microstructures toward high‐performance NFA OSCs. Abstract : A photovoltaic layer consisting of bicontinuous phase‐separated networks of polymer donor and Y6 acceptor along with highly ordered nano‐sized Y6 aggregates can effectively enhance charge generation via hole transfer by increasing the intra‐moiety excited states from acceptor domains, which enables a high efficiency of 17.98% in D18:Y6‐based organic solar cells.